Dynamic expression of 11 miRNAs in 83 consecutive primary and corresponding recurrent glioblastoma - Matos, Boštjan (Radiology and oncology (Ljubljana), 2018)
Background. Glioblastoma (GBM) is the most common and the most malignant glioma subtype. Among numerous genetic alterations, miRNAs contribute to pathogenesis of GBM and it is suggested that also to GBM recurrence and resistance to therapy. Based on publications, we have selected 11 miRNAs and analyzed their expression in GBM. We hypothesized that selected miRNAs are differentially expressed and involved in primary as well as in recurrent GBM, that show significant expressional differences when different treatment options are in question, and that are related to certain patients and tumor characteristics. Patients and methods. Paraffin embedded tissues, obtained from primary and corresponding recurrent tumor from 83 patients with primary GBM were used. Eleven miRNAs ( miR-7, miR-9, miR-15b, miR-21, miR-26b, miR-124a, miR-199a, let-7a, let-7b, let-7d, and let-7f ) were selected for qPCR expression analysis. For patients who received temozolamide (TMZ) as chemotherapeutic drug, O6-methylguanine-DNA methyltransferase (MGMT) methylation status was defined using the methyl-specific PCR. Results. There was a significant change in expression of miR-7, miR-9, miR-21, miR-26b, mirR-124a, miR-199a and let- 7f in recurrent tumor compared to the primary. In recurrent tumor, miR-15b, let-7d and let-7f significantly changed comparing both treatment options. We also observed difference in progression free survival between patients that received radiotherapy and patients that received radiotherapy and chemotherapy, and longer survival for patients who received chemotherapy after second surgery compared to not treated patients. miR-26b showed correlation to progression free survival and let-7f to overall survival. We did not find any expression difference between the tumors with and without methylated MGMT. Conclusions. Our data suggest that analyzed miRNAs may not only contribute to pathogenesis of primary GBM, but also to tumor progression and its recurrence. Moreover, expression of certain miRNAs appears to be therapy- dependent and as such they might serve as additional biomarker for recurrence prediction and potentially predict a therapy-resistance.
Keywords: glioblastom; kemoterapija; molekularna genetika; radioterapija